Development of the compensation method of pressure pulsation effect on the multi-stage hydraulic cylinder motion - Чуйко, Всеволод Петрович; Кулініч, Сергій Павлович (Eastern-European Journal of Enterprise Technologies, 2014)
An example of the hydraulic wrench application is a maintenance process, associated with the main circulation pump jack at a nuclear power plant. Mathematical model of the hydraulic drive with two coaxial hydraulic cylinders is investigated to solve the problem of uncontrolled changes in the hydraulic drive system characteristics. The mathematical model considers the parallel connection of discharge chambers, nonlinear flow from the one-piston pump, fluid compressibility, the friction force between the actuator components. The drive operation is investigated at a full rotation of the feed pump crank. The system includes a throttle on the drain line in order to overcome negative hydrodynamic processes. The characteristics of the drive are investigated, and the throttle characteristics are defined to overcome pulsation. The values of the throttle opening area are determined for each time point, at a constant speed of the drive. Obtained matrix values are regarded as a law, and the speed becomes a calculated value, used to verify the results. Calculations have confirmed the possibility of providing the drive rod velocity, which is close to constant. Further development of the results provides a synthesis of the law of the throttle closing changes. It will provide the technological feasibility for manufacturing and ensure linear, close to constant, effort, generated by the hydraulic drive.